Pain and culture - on cultural communications of suffering - Sachs, Lisbeth (Journal of Sports Medicine and Therapy, 2022)
The impact of culture on the communication of pain becomes visible in a comparative perspective when individuals with two different cultures meet. Regardless of the physiological cause, it is through lived experience, in social life, that it is decided how, where, when and for whom pain is to be communicated. Age and gender, situation and context as well as the type of pain are essential ingredients in communication. The communication is always adapted to expectations from those present, their own experiences of pain and the specific circumstances, the cause of the pain. The impact of culture on the communication of pain becomes visible in a comparative perspective when individuals with two different cultures meet.